Black Trackers: Labour Contributions of Aboriginal People in the Hunter Region of New South Wales, 1804–54. (1st May 2018) - Blyton, Greg
Abstract : This article identifies the important work of Aboriginal people dubbed in colonial ethnography as "black trackers" with a specific focus on their work as agents of colonial law enforcement in the Hunter region of New South Wales between 1804 and 1854. Within Australian historiography the roles and occupation of black trackers are somewhat blurred with the native police forces. The article shows that the role and occupation of black trackers differed from that of the native police forces who were employed by colonial governments during the same period. While the importance of "black trackers" in Australian history in the nineteenth century is recognised in popular literature and cinema, there are few if any regional studies and none which explore this work as an aspect of Australian labour history. This article adds to knowledge of the role of black trackers as casual labour supporting soldiers, police, magistrates and civilian posses in pursuit of escaped convicts and bushrangers. In the focus on the Hunter region, it argues that black trackers' labour was important in assisting settlers as well as protecting their own communities by apprehending fugitive European felons.